On reconciliation - Springer, Anna-Sophie; Arendt, Hannah; Heidegger, Martin (Berlin : K. Verlag, 2018)
A series of reflections on the correspondence between Hannah Arendt and Martin Heidegger, from 1925 to 1975, as a means to think about moral responsibility, ethical indebtedness, and the role of intellectuals in times of political urgency. These reflections were initiated by Dora Garcia, who was joined by Simon Asencio, Rebecka Katz Thor, Nikola Mirkovic, Anna-Sophie Springer, Mark Thomas, Yuliya Tsutserova, Etienne Turpin, and Adriano Wilfert Jensen.
Parallel texts in English and German.
Following the exhibition "Performing grounds: performance as situation, installation, and sculptural intervention" held at the Gallery for Contemporary Art, E-Werk, Freiburg, September 10-October 2, 2016; launched on the occasion of the exhibition "Dora Garcia: second time around", Museo Reina Sofia, Madrid, June 28, 2018.
boek
Keywords: Garcia, Dora